Vegetation structure and floristic composition of tree species in the habitat of Scaphium macropodum in Gunung Leuser National Park, Sumatra, Indonesia - ARIDA SUSILOWATI; DENI ELFIATI; HENTI HENDALSTUTI RACHMAT; KUSUMADEWI SRI YULITA; ADI NURUL HADI; YOSIE SYADZA KUSUMA; SRI ANJELI LUMBAN BATU (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Susilowati A, Elfiati D, Rachmat HH, Yulita KS, Hadi AN, Kusuma YS, Batu SAL. 2020. Vegetation structure and floristic composition of tree species in the habitat of Scaphium macropodum in Gunung Leuser National Park, Sumatra, Indonesia. Biodiversitas 21: 3025-3033. Scaphium macropodum (Miq.) Beumee Ex K Heyne is a member of Malvaceae tree species and globally recognized as malva nut and locally known as ‘kembang semangkok’, ‘tempayang’, ‘merpayang’ or ‘kepayang’. The nut of S. macropodum has many benefits for medicinal purposes, yet destructive extraction of this tree species has led them to extinction. Among its natural distribution in Indonesia, North Sumatra Province, Indonesia is known as its original range, but there is limited information about the existence of this species. This study aimed to determine the vegetation structure of some tree species in the habitat of S. macropodum in Sikundur, Gunung Leuser National Park, Sumatra, Indonesia. Purposive sampling technique was employed by creating line transect at some forest areas where the population of S. macropodum is known to grow naturally. Four line transects with each transect consisting of five plots with nested plots within were established to record data at four growth stages, resulting in 80 plots in total. The results showed that the Important Value Index (IVI) of S. macropodum within the floristic community at the studied area was 21.98, 13.85, 27.30, and 39.60 for tree, pole, sapling, and seedlings stages, respectively. The Shannon-Wiener Diversity Index (H) were 3.80, 3.70, 3.06 and 2.45, Index of evenness (E) are 0.94, 0.92, 0.86, 0.77 and the Index of Richness (R) are 11.76, 10.73, 6.59, 4.10 for tree, pole, sapling, and seedlings stages. This result suggests that the natural population of S. macropodum in Sikundur forest was still in good condition at all stages from tree to seedling.